The impact of brand equity dimension toward customer purchasing intention on proton cars in Shah Alam / Nur Ashyikin Abdul Latif - Abdul Latif, Nur Ashyikin (Bachelor of Science (Hons) Statistics, 2015)
The study is focused on investigating the impact of brand equity dimensions towards customer purchasing intention on PROTON cars. These brand equity dimensions are divided into four that include brand awareness, brand association, brand loyalty and perceived quality on brand. All of brand equity dimensions will be an independent variable, while purchasing intention is dependent variable. The objective of study is to investigate the relationship between brand equity dimensions towards customer purchasing intention on PROTON cars and to investigate the difference in mean customer purchasing intention between difference customers’ demographic profile. The variable interest for the study are age group, race, marital status, education, occupation, income and the period using PROTON cars. Questionnaire was the main instrument for this study. The data obtained from customer who came to service center on November 2014 which were analyzed using Test of Reliability, Confirmatory Factor Analysis (CFA), Structural Equation Modelling (SEM) and Analysis of Variance (ANOVA). The equation was employed by using Analysis of Moment Structure (AMOS) and Statistic Package for Social Science (SPSS) software. The result of the analysis revealed that there is relationship two out of four the modelled independent constructs tested with customer purchasing intention which are brand loyalty and perceived quality of brand. For brand awareness and brand association, they does not have significant relationship towards customer purchasing intention. In addition, the study also found that there is difference in mean customer purchasing intention on PROTON cars between Malay, Chinese, Indian and others. The research finding will provide an enlightening insight for carmakers manufacturers, marketing manager and academicians